Opera buffa und Spielkultur Eine spieltheoretische Untersuchung am Beispiel des venezianischen Repertoires des späten 18. Jahrhunderts - Schraffl, Ingrid (2014)
The ludic element contributes substantially to the highly entertaining quality of opera buffa. Within the field of opera research, up to now this aspect has been neglected to a large extent. However, the denomination itself of the buffa-genre usual in the 18th century - "dramma giocoso" - typifies the central role of the playful element in this opera form. On the basis of play theories derived from different disciplines - anthropology, psychology, pedagogy and philosophy - the multilayered moments of play in the opera buffa and its performance context are enucleated by analysing the repertory of Venice, the then "capital of amusement". Thereby, the concept of play is used as an interpretive key applied to this cultural phenomenon as a whole.